2021
DOI: 10.4103/ijo.ijo_3463_20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and rotational stability following implantation of Eyecryl toric intraocular lens – Results of a 12-months prospective study

Abstract: Purpose: To evaluate the clinical performance and rotational stability after implantation of Eyecryl Toric monofocal IOL following cataract surgery. Methods: Patients undergoing phacoemulsification for age-related cataract and satisfying the eligibility criteria were implanted with Eyecryl Toric IOL. All implantations were done under balanced salt solution. A marker-less system Callisto Eye (Carl Zeiss Meditec, Germany) was used to guide the intra-operative alignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…According to the findings of our study, patients with corneal astigmatism who had toric AcrySof and Eyecryl IOLs implanted after cataract surgery saw comparable visual results and astigmatism reduction, which are in line with similar studies. [ 1 4 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] Nevertheless, this study is the first to directly examine the results of a known international toric IOL, such as AcrySof toric, with those of an Indian-made toric IOL, Eyecryl, in a secondary center in South India. Post-operative UCVA at 1 month was comparable between the two toric IOLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings of our study, patients with corneal astigmatism who had toric AcrySof and Eyecryl IOLs implanted after cataract surgery saw comparable visual results and astigmatism reduction, which are in line with similar studies. [ 1 4 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] Nevertheless, this study is the first to directly examine the results of a known international toric IOL, such as AcrySof toric, with those of an Indian-made toric IOL, Eyecryl, in a secondary center in South India. Post-operative UCVA at 1 month was comparable between the two toric IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…An IOL rotation of more than 10 degrees post-operatively was discovered in up to 7% of eyes across several studies involving all commonly used toric IOLs, with a high axial length, a younger age, greater pre-surgical astigmatism, and with the rule astigmatism patients having the highest rotation within the first 10 days post surgery. [ 9 10 11 12 18 20 21 22 24 29 30 43 44 ] IOL rotation less than 10 degrees typically does not require re-surgery. It has been found that hydrophobic acrylic lenses have better rotational stability than other IOL materials.…”
Section: Discussionmentioning
confidence: 99%